Image of “Fallen Woman” in Novels of G. Fallada’s “Wolf Among Wolves” and F. M. Dostoevsky’s “Crime and Punishment”: Comparative Analysis - L. A. Melnikova (Научный диалог, 2023)
The image of the “fallen woman” in the novels of G. Fallada’s “Wolf Among Wolves” and F. M. Dostoevsky’s “Crime and Punishment” is examined. Traces of the literary influence of the Russian classic on the poetics of the German writer’s novel at the thematic and character levels are identified. It is established that the key motif in both works is the theme of moral resurrection of the fallen individual. It is shown that, in addressing the problem of the “humiliated and insulted”, both authors incorporate the image of the “fallen woman” into the system of characters in their novels. It is noted that the writers pay special attention to the reasons for her social downfall. Through the use of comparative-historical analysis, parallels in the images of “fallen” women presented in these works — Petra Ledig and Sonya Marmeladova — are identified. The author of the article concludes that the heroines share a number of common features: Christian semantics of their names, moral purity despite physical vice, a tendency towards selfsacrifice, great inner strength despite outward timidity, a desire to show mercy, the ability to motivate their loved ones towards spiritual rebirth and thereby “rebirth” themselves. The results of the study allow to demonstrate the significance of F. M. Dostoevsky’s humanistic ideas for the aesthetic principles and worldview position of G. Fallada in the novel “Wolf Among Wolves”.